Transport of Low Molecular Weight Proteins through Aorta and Vena Cava of Rats and Rabbits - Pinkas, J; Spaet, Th. H (Thrombosis and Haemostasis, 1972)
Histochemical methods were adapted to study the passage of different sized molecules through the aortic wall of rats and rabbits. Horseradish peroxidase, myoglobin and cytochrome C served as tracers of different molecular weights easily identifiable by light microscopy after peroxidase staining. All three proteins were transported from the lumen through the aortic wall to the adventitia; no penetration from the adventitia was seen. When compared for rate of transportation, horseradish peroxide with the highest molecular weight was slower than myoglobin and cytochrome C. In the vena cava the transport of these proteins occurred from both directions but the media was saturated from the lumen only. No difference between velocity of transport of horseradish peroxidase, myoglobin and cytochrome C was found in the vena cava. In vitro incubation in various solutions containing dissolved horseradish peroxidase showed penetration of peroxidase to be minimal. The molecular weight of material transported and pressure in the lumen are considered as the most important factors influencing the transport of nutrients through the wall of an avascular large vessel. When abdominal aorta was isolated from surrounding tissue, clearance of peroxidase from the vessel wall was greatly retarded.